The effect of El Nino and La nina on the rain data of Lampung Barat Regency, Lampung Province - Hartantio, Fajar; Zakaria, Ahmad; Kusumastuti, Dyah (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
The purpose of this research to analyze and determine dominant impact area due to the effect of El Nino and La Nina on 6 rainfall station in west Lampung Regency, Lampung Province. This study also compred between Fast Fourier Transform (FFT) methods, and Lomb Periodogram methods. This study using rainfall data from 1998 to 2019 taken from Balai Besar Wilayah Sungai Mesuji – Sekampung (BBWSMS). According on comparison result, it is known that both methods indicate that Air Hitam Rainfall Station experience the effect of El Nino and La Nina more dominantly than the others, with the looping period of 3,9165 years from Lomb Periodogram method and 3,7381 years from (FFT) Method. It is also known that Lomb Periodogram Method has a better accuracy than (FFT) method. This is because Lomb Periodogram can read the length of data more accurately than Fast Fourier Transform (FFT) method.  Keywords: El Nino, La Nina, rain station, rainfall, Fast Fourier Transform, Lomb Periodogram